Does 1, 8-diiodooctane affect the aggregation state of PC71BM in solution?. Issue 9 (12th September 2018) - Bernardo, Gabriel; Washington, Adam. L.; Zhang, Yiwei; King, Stephen. M.; Toolan, Daniel. T. W.; Weir, Michael P.; Dunbar, Alan D. F.; Howse, Jonathan R.; Dattani, Rajeev; Fairclough, John Patrick A.; Parnell, Andrew J.
Abstract : 1, 8-Diiodooctane (DIO) is an additive used in the processing of organic photovoltaics and has previously been reported, on the basis of small-angle X-ray scattering (SAXS) measurements, to deflocculate nano-aggregates of [6, 6]-phenyl-C71-butyric acid methyl ester (PC71 BM) in chlorobenzene. We have critically re-examined this finding in a series of scattering measurements using both X-rays and neutrons. With SAXS, we find that the form of the background solvent scattering is influenced by the presence of DIO, that there is substantial attenuation of the X-rays by the background solvent and that there appears to be beam-induced aggregation. All three factors call into question the suitability of SAXS for measurements on these samples. By contrast, small-angle neutron scattering (SANS) measurements, performed at concentrations of 15 mg ml −1 up to and including 40 mg ml −1, show no difference in the aggregation state for PC71 BM in chlorobenzene with and without 3% DIO; we find PC71 BM to be molecularly dissolved in all solvent cases. In situ film thinning measurements of spin-coated PC71 BM solution with the DIO additive dry much slower. Optical imaging shows that the fullerene films possess enhanced molecular mobility in the presence of DIO and it is this which, we conclude, improves the nanomorphology and consequently solar cell performance. We propose that any compatible high boiling solvent would be expected to show the same behaviour.